AKAL (Antisipasi Kanker pada Lansia): Improving Public Knowledge of Cancer in Yogyakarta - Arief, Thendi Abdul; da Costa, Yohanna Lawanda; Budiarti, Niky; Hadi, Paulina Ambarsari Mawar Ning; Pertiwi, Luthfiah (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2026)
The incidence of cancer in the elderly population is increasing as life expectancy rises. In addition, the number of elderly patients with cancer has increased and is expected to continue to grow with advances in cancer treatment. Cancer commonly develops in elderly people aged ≥55 years. This study aimed to improve the elderly’s knowledge of cancer prevention. This observational, cross-sectional study was conducted in RW 23, Brontokusuman Village, Yogyakarta, and targeted the elderly who were members of the Pemberdayaan Kesejahteraan Keluarga/PKK (Family Welfare Empowerment). This activity included a pretest, followed by education delivered through direct presentations, and a posttest to evaluate outcomes after the educational intervention. A sample of 34 participants was recruited using accidental sampling. Data were analyzed using univariate analysis as well as descriptive statistics through mean, median, mode, and percentage. The results showed that the most common age group was 51–60 years (44.12%). The mean knowledge score increased from 76.47 to 91.47, with a p value of 0.000, indicating a significant improvement in knowledge before and after cancer prevention education. The greatest increases in understanding were observed for questions 10, 8, 2, and 6, respectively. Several topics demonstrated a substantial improvement, particularly those that were previously poorly understood. Community-based education may be an effective strategy for cancer prevention, particularly for the elderly population.